Construction and characterization of a CO2 wave guide laser with a special electrode design for materials processing - Jiménez Pérez, J. L.; Algatti, M. A. [UNESP]; Mendoza-Alvarez, J. G.; Cruz Orea, A. (SPIE, the international society for optics and photonics, 2001)
We describe the design and construction of an efficient tunable CO2 wave guide laser which was used for thermal graving of predigitalized images over polymeric materials. The small internal diameter of the cylindrical wave guide allowed the laser operation in high pressure regime ranging from 50 Torr to 100 Torr, which gives higher gain per cavity length. The operation of the laser at 80 Torr with the gas composition CO2:N2:He
Keywords: Gas lasers; Industrial applications; Optical waveguides